Co-infection and Risk Factors Associated with STIs among Pregnant Women in Rural Health Facilities in Nigeria: A Retrospective Study. (March 2021) - Umoke, MaryJoy; Sage, Peter; Bjoernsen, Tor; Umoke, Prince Christian Ifeanachor; Ezeugworie, Christian; Ejiofor, Daniel; Agha, Ogbonna; Nwalieji, Chioma Adaora; Onwe, Rosemary N.; Nwafor, Ifeanyi Emmanuel; Chukwu, Obinna Jude
Globally, sexually transmitted infections are recognized as a public and reproductive health challenge. The study determined the prevalence, co-infection, and risk factors associated with HBV, HCV, HIV, and Syphilis infections among pregnant women receiving antenatal care in rural health facilities in Ebonyi State, Nigeria. A retrospective study was conducted from January to December 2018 in 8 primary healthcare facilities using antenatal records of all the 4657 pregnant women who attended ANC within the period. Data were analyzed using descriptive and inferential statistics with IBM SPSS statistics version 20 and hypotheses tested at P < .05. The findings indicated a medium prevalence of HBV (4.1%), a high prevalence of HCV (4.1%) and syphilis (1.8%), and a low prevalence of HIV (0.9%). An overall co-infection rate of 0.623% that was not significant ( P > .05) was observed. Also, prevalence was more among the younger mothers (<20 years), those with secondary education. And the history of blood transfusion was significantly associated with HBV and HCV prevalence (χ 2 = 7.865; P = .05*), 11.8%. conclusively, due to medium HBV prevalence and a high prevalence of HCV and syphilis observed, attention should be paid to blood screening before transfusion by health workers. Relevant stakeholders should provide intensive health education and appropriate free treatment services particularly for younger mothers and the less educated.